Microbubble-mediated delivery for cancer therapy - Browning, R; Stride, E (MDPI, 2018)
Despite an overall improvement in survival rates for cancer, certain resistant forms of the disease still impose a significant burden on patients and healthcare systems. Standard chemotherapy in these cases is often ineffective and/or gives rise to severe side effects. Targeted delivery of chemotherapeutics could improve both tumour response and patient experience. Hence, there is an urgent need to develop effective methods for this. Ultrasound is an established technique in both diagnosis and therapy. Its use in conjunction with microbubbles is being actively researched for the targeted delivery of small-molecule drugs. In this review, we cover the methods by which ultrasound and microbubbles can be used to overcome tumour barriers to cancer therapy.